Heahgetimbru: A Reassessment of Christ III ll. 972–6 - Bailey, H (Oxford University Press, 2016)
A misunderstanding of the referent of the compound heahgetimbru in l. 973b of Christ III has resulted in confusion over the denotation of the sentence in which it appears and also obscured the artistry in the structure of the larger passage in which it appears.